To Work or not to Work: Factors Affecting Bridge Employment Beyond Retirement, Case of Lithuania - Zitikytė, Kristina (Ekonomika, 2020)
This paper investigates bridge employment beyond retirement, as nowadays it is one of solutions often mentioned to stabilize pension systems in the context of an aging population. The aim of this paper is to identify individual, financial, and other factors that influence retirees to work beyond retirement in Lithuania. This research was done using unique administrative Lithuanian data, allowing to analyze post-retirement employment in Lithuania for the first time. The sample consists of 26,000 new old-age pension recipients from 2015 to 2017. By applying binary models of the probability of being employed beyond retirement, it is found out that a greater acquired retirement record, a higher average wage before retirement, and living in a bigger city with a higher employment rate were positively associated with accepting bridge employment, while a higher sickness rate, higher old-age pension, and earlier receipt of an unemployment benefit were inversely related to accepting such employment. Moreover, being a professional or manager increases the likelihood of bridge employment in comparison to unskilled workers. This probability increases even more if a person works in the public sector. Finally, some social groups were excluded, finding that widows with disabilities or widowed women with worse health are not likely to work beyond retirement and are consequently under a bigger risk of poverty. To sum up, retirees who should stay in the labor market in their old age because of their bad financial situation are less likely to do it. This suggests that persons with bigger needs, lower-skilled workers, and women deserve particular attention in labor market reforms.